Human well-being, morality and the economy: An Islamic perspective - Haithem Kader (Islamic Economic Studies (IES), 2021)
Purpose This study argues that in order to address the problems associated with the modern market economy at their core, such as persistent poverty, growing inequality and environmental degradation, it is imperative to re-assess the well-being and moral philosophy underpinning economic thinking. The author attempts to offer a preliminary way forward with reference to the Islamic intellectual tradition. Design/methodology/approach This study employs content analysis of classical and contemporary Islamic texts on human well-being and economic ethics to derive a conceptual well-being model. The paper is structured in four sections: section one provides an overview of relevant secondary literature on moral economic approaches; section two outlines the main well-being frameworks; section three discusses the concept of human well-being in Islam informed by the Islamic worldview of tawhid, the Islamic philosophy of Sa'adah, and the higher objectives of Islamic Law (Maqāsid al-Sharī'ah); and finally, section four discusses policy implications and next steps forward. Findings A conceptual model of human well-being from an Islamic perspective is developed by integrating philosophical insights of happiness (Sa'adah) with an objective list of five essential goods: religion (Dīn), self (Nafs), intellect ('Aql), progeny (Nasl) and wealth (Māl) that correspond to spiritual, physical and psychological, intellectual, familial and social, and material well-being, respectively. Research limitations/implications Further research is needed to translate this conceptual model into a composite well-being index to inform policy and practice. Practical implications This model can be used to review the performance of the Islamic finance sector, not solely in terms of growth and profitability, but in terms of realising human necessities, needs and refinements. It can also provide the basis for the Organisation of Islamic Co-operation (OIC) countries to jointly develop a well-being index to guide national and regional co-operation. More generally, this study highlights the need for research in Islamic economics to be more firmly rooted within Islamic ontology and epistemology, while simultaneously engaging in productive dialogue with other moral schools of economic thought to offer practical solutions to contemporary challenges. Originality/value This study offers three aspects of originality. First, by outlining well-being frameworks, it highlights key differences between the utilitarian understanding of well-being underpinning modern economic theory and virtue-based understandings, such as the Aristotelian, Christian and Islamic approaches. Second, it provides a well-being model from an Islamic perspective by integrating the Islamic worldview of tawhid, the Islamic philosophy of Sa'adah, and the higher objectives of Islamic Law (Maqāsid al-Sharī'ah). Third, it proposes an ethical framework for informing economic policy and practice.
Keywords: B0; O1; P4; 330; Maqāsid; Moral economy; Sa'adah; Well-being